PELATIHAN PEMBUATAN ZONA LAMBUNG PERAHU IKAN FIBERGLASS SKALA KECIL PADA DESA PABEAN UDIK KECAMATAN INDRAMAYU - Amir Marasabessy; Fajri Ashfi Rayhan; Fakhri Akbar Ayub; Wiwin Sulistyawati; Rusdy Hatuwe (Jurnal Bakti Masyarakat Indonesia, 2023)
Fishermen group from Pabean Udik village, Indramayu, have problems with the maintenance of wooden boat hulls. Limitations of wood resources and the management of ships owned by skippers are a source of problems for fishermen in the Pabean Udik village. The objective of this project is to provide education and training for the manufacture of small-scale fiberglass fish boat hull for fishermen in Pabean Udik village. Iit was an effort to empower the fishing village community of Pabean Udik village to be able to make fiberglass fishing boats independently, as well as a transition from using fishing boats made of wood to fiberglass. The methods used were semi-permanent moulded and hand laid-up. In this case, the mat and roving layers are laminated using a hand brush or roll brush. This activity process involved a team of lecturers, students of Universitas Pembangunan Nasional Veteran Jakarta, practitioners and 10 fishermen from the village of Pabean Udik.The results of this work were the hull products of small-scale fish boats made of fiberglass with dimensions of length (P) = 1.0 m, width (B) = 0.5 m, and height (H) = 0.3 m. The conclusion of this study was that the fishing community of Pabean Udik village got new insights into the manufacture of fiberglass-based fishing boats. Therefore, in the future, the fishing community of Pabean Udik village can produce their own fishing boats with fiberglass.